Deploying sustainability at Solea - Bell, Jan, (SAGE Knowledge. Cases., 2017)
Solea, a multinational food and facilities management company, announced a global sustainability initiative. Within Solea, sustainability meant considering the environmental and social impacts of operations along with profitability. This case focuses on how the implementation of the sustainability initiative created organizational conflict between the sustainability group and the supply management group. Most of the disagreement arose from supply management strategies, designed to increase immediate profits, which conflicted with sustainability strategies, aimed to yield longer-term impacts. Even with upper management supporting sustainability, the case demonstrates how complicated it is to implement sustainability when actions get in the way of immediate profits and financial data is missing. Students understand the need to explicitly link (map) the new strategy to financial performance metrics, to specify when and how the benefits of a new strategy should impact profitability, and to monitor lead and lag performance measures.